Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/1082013219833234
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, antioxidant and microbial properties of crystallized pansies (Viola × wittrockiana) during storage

Abstract: Edible flowers, such as pansies, have a short shelf-life. Crystallization is a treatment used to prolong the shelf-life of fruits and vegetables. So, the aim of the present work was to investigate the effect of crystallization in the physicochemical, microbial and antioxidant properties of pansies ( Viola×wittrockiana) during room temperature storage (7, 15, 30, 60 and 90 days). Comparing fresh and crystallized pansies, significant differences were detected. After 90 days of storage, crystallized pansies kept … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Similar DPPH inhibition was found by González-Barrio et al in a V. x wittrockiana flower extract obtained by maceration (71.20%) [ 5 ]. Besides, our results seem to be better to the data obtained for V. x wittrockiana carried out by Fernandes et al [ 23 , 24 ].…”
Section: Resultssupporting
confidence: 76%
“…Similar DPPH inhibition was found by González-Barrio et al in a V. x wittrockiana flower extract obtained by maceration (71.20%) [ 5 ]. Besides, our results seem to be better to the data obtained for V. x wittrockiana carried out by Fernandes et al [ 23 , 24 ].…”
Section: Resultssupporting
confidence: 76%
“…Previous studies on this edible flower have focused mainly on its antioxidant activity, and also its neuroprotective potential. 24–28…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on this edible flower have focused mainly on its antioxidant activity, and also its neuroprotective potential. [24][25][26][27][28] Caenorhabditis elegans is a nematode widely used as an animal model for research in very diverse fields. Along with its many advantages such as easy handling and storage, it has been found that approximately 80% of human protein-coding genes had homologues in the C. elegans proteome.…”
Section: Introductionmentioning
confidence: 99%
“…The wide variety of species, different flowering times and different organoleptic properties contribute to the great potential and applicability of flowers in many industries. In the food industry and gastronomy, they are used as garnishing as well as an integral part of the meal [14]; they can be used fresh (in salads, cocktails, and even meat dishes), dried (as infusions, dessert garnishing, e.g., dried rose or cornflower petals), powdered, crystallised or as foam (molecular gastronomy) [16,17]. Chefs around the world reach beyond the ordinary when coming up with new recipes.…”
Section: Introductionmentioning
confidence: 99%